Enrichment And Characterization Of Limonin Degrading Microorganisms Isolated From Kinnow Orchard Soil, Peel And Waste Site (Applied Biological Research, 2017)
The present research was aimed to screen and characterize limonin  degrading microorganisms and assess their efficiency in limonin reduction.  ight bacterial isolates from kinnow orchard soil and two yeast isolates from  soft kinnow peel and kinnow waste site (Abohar, Punjab) were isolated. All  the isolates were evaluated for their limonin utilizing ability by swarm plate  assay. Two bacterial isolates (S1 and S2) and both yeast isolates (PY1 and  AY1) showed considerable zone of TTC reduction. All the four selected  isolates were studied for their growth profile and rate of limonin degradation  in minimal media broth with limonin (28 ppm) as a sole carbon source.  Bacterial isolate S1 showed maximum limonin degradation (52.9%), followed by yeast isolates PY1 (48.5%), AY1 (31.1%) and bacterial isolate S2 (26.4%).  Ca-alginate immobilized cells of PY1 yeast and S1 bacteria were also studied for their limonin degrading ability which respectively showed 94.8 and 98%  limonin reduction. The two microbial isolates were molecularly identified as Bacillus megaterium strain KU570370.1. on 16SrDNA basis and Meyerozyma  caribbica isolate KP860076.1. on 18S rDNA basis These microbial isolates  could be exploited for the production of enzyme limonin dehydrogenase for  possible use in debittering kinnow juice.
Keywords: Bacillus megaterium; degradation; immobilized cells; limonin; Meyerozyma caribbica